In vitro development of salt tolerant Malaysian indica rice ‘MARDI Siraj 297’ and enhancement of salinity tolerance using salicylic acid - Sidek, Noorhazira; Nulit, Rosimah; Chee, Kong Yap; Seok, Christina Yien Yong; Sekeli, Rogayah (Instituto de Investigaciones Agropecuarias, INIA, 2024)
Among cereal crops, rice (Oryza sativa L.) is the most susceptible to salinity. Due to emerging salinity impacts on food security, different strategies have been implemented including developing salt tolerant varieties. Therefore, this study was conducted to produce salt tolerant lines of ‘MARDI Siraj 297’ through in vitro callus selection, enhancement of salinity tolerance through supplementation of salicylic acid (SA) (0, 0.5 and 1.0 mM) and regeneration of the selected salt tolerant callus. Embryogenic calli were induced and then treated in selection medium containing 0, 25, 50, 75, 100, 125 and 150 mM NaCl for 5 mo, followed by screening and selection of salt tolerant variants using morphology and biochemical parameters associated with salt tolerance. The salt tolerant calli showed reduced tissue necrosis and maintain their viability. Biochemical profile of these salt tolerant calli showed significantly (p < 0.05) higher content of proline (0.28 to 0.38 mg g-1), total soluble sugar (6.4 to 12.9 mg g-1), catalase activity (0.9 to 8.0 μmol min-1 mg-1 protein), ascorbate peroxidase activity (5.4 to 20.3 μmol min-1 mg-1 protein), malondialdehyde (6 to 17 μg g-1 protein) and K+/Na+ ratio (1.0 to 3.0) while reduced in protein content as compared to the non-tolerant control. These characteristics are typically associated with tolerance against salinity, therefore lines potentially tolerant to this stress have been regenerated. The selected salt tolerant calli were transferred into medium with SA to enhance their tolerance. Supplementation of 1.0 mM SA results in reduced morphological injury, higher regeneration frequency and shoot number (56% and 6 shoots, respectively) as compared to the non-SA-treated. Hence, this study demonstrates the protective effect of SA against salinity and provides a reliable protocol for establishment of salt tolerant rice lines through in vitro selection.